Business investment decision tools. User guide - Rajendran, S.; Jayanth, R.; Martin, O. (2024)
Business Investment Decision (BID) Tools are designed to provide a comprehensive, modular digital platform for business enterprises in order to empower them with structured decision-making frameworks for financial planning, investment analysis, and business growth. These tools were developed through the Seed Equal Initiatives Project of the CGIAR. The tool enables business enterprise operators to be able to develop an operational business plan inclusive of your business details, business environments (SWOT & PESTEL Analysis), Business Models (Value Proposition Canvas, Value Maps & Business Model Canvas), Operations (Product workflows), financial management (variable costs & fixed costs), sales projections, Partnership Development and Business Risk Management. Business details fed into the system is used to generate the full business plan and financial reports as seen in the user guide. The BID tools comes in two versions; 1. Web version; accessible through http://bidtool.cipotato.org or https://mt.co.ug/bid_tools_bplan 2. Excel Version which is downloadable through the same web links above The BID Tool is divided into ten important modules; 1. Business Background 2. Business Environment 3. Business Model 4. Operations (Workflows and Stages) 5. Financial Management a. Costing b. Financial Statements c. Ratio analysis 6. Budgeting 7. Valuation 8. Diagnostic Report 9. Partnership 10. Risk Management